Groundwater quality parameters for irrigation utilization - DIMPLE,; MITTAL, HEMANT KUMAR; SINGH, PRADEEP KUMAR; YADAV, K K; BHAKAR, SITA RAM; RAJPUT, JITENDRA (The Indian Journal of Agricultural Sciences, 2022)
Globally, groundwater is utilized indiscriminately to fulfill the water demands of different sectors. This uncontrolled use has amounted to a downward trend in the groundwater table and the imbalance of this vital resource quantity and quality in the environment. Groundwater quality is crucial not only to human health but also to optimize crop yields. Human-induced contaminants andÂ insufficient correctiveÂ measures degrade groundwater quality. This article reviews various water quality parameters for irrigation and the impacts of low-quality water on crop yield and soil properties. Water quality is quantified and analyzed as per the water's intent. Indicators for the water quality evaluation include, in particular, the salinity hazards, sodium hazard, salt level, alkalinity hazards, permeability hazards, and ion-specific toxicity hazards. Improper irrigation water use has, in some cases, disordered soil and water quality. Proper attention must be given to manage low water quality and adequate drainage for soil affected by salts. This review paper illustrates the key parameters that affect crop yield and soil quality. This review article aims to enable the reader to comprehend better the effects of water quality on Soil and crops and guide in deciding appropriate possible solutions to address probable water quality threats that could lower yield under prevalent use conditions